Coronavirus Environment vs Socio-Economic and Demographic Problems Followed: A Sociological Appraisal - Mohammad Taghi Sheykhi (Budapest International Research and Critics University, 2020)
The paper searches the cause and effect impacts of the newly-found Coronavirus. The word